If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -6 = 5y + 15 + -21 Reorder the terms: -6 + 3y = 5y + 15 + -21 Reorder the terms: -6 + 3y = 15 + -21 + 5y Combine like terms: 15 + -21 = -6 -6 + 3y = -6 + 5y Add '6' to each side of the equation. -6 + 6 + 3y = -6 + 6 + 5y Combine like terms: -6 + 6 = 0 0 + 3y = -6 + 6 + 5y 3y = -6 + 6 + 5y Combine like terms: -6 + 6 = 0 3y = 0 + 5y 3y = 5y Solving 3y = 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 3y + -5y = 5y + -5y Combine like terms: 3y + -5y = -2y -2y = 5y + -5y Combine like terms: 5y + -5y = 0 -2y = 0 Divide each side by '-2'. y = 0 Simplifying y = 0
| a^2+31=607 | | -5=3x+4+6x | | f^2+64=353 | | w^2+97=113 | | 5+3-2m+3(6+3m)=7m+3(5m-2) | | x+x+5=39 | | -7+5=-11x+17 | | 6x^2+11=49 | | 17x=100 | | -10x+-30=-8x | | 6x+4y+7z-4x+5z-8y= | | 150=2x^3+x^2+x+10 | | H=15t | | B=1.0 | | y-.666666667=5 | | 4(v-9)=-6v+34 | | 2x+7*-1=5 | | -31x-4x=-5-5+25x | | -10x=-8x-8 | | 28x^3+48x^7= | | (x-1)/2/5/4 | | 4n-6+4n=2 | | 9x^4-24x^3-26x^2+56x-15=0 | | 4x^2-11=26 | | f(x)=9x^4-24x^3-26x^2+56x-15 | | 49v-90=-6v+34 | | -5-8=5x+9x-21x | | 192=3X | | -8x^2=-64 | | (1-4x)(1-3x)=6x(2x-1) | | 6,5/9=x/40 | | (5y+4w-3w-5)= |